Oxytocin as a Modulator of Synaptic Plasticity: Implications for Neurodevelopmental Disorders - Rajamani, Keerthi Thirtamara; Wagner, Shlomo; Grinevich, Valery; Harony-Nicolas, Hala (Frontiers in Synaptic Neuroscience, 2018)
The neuropeptide oxytocin is a crucial mediator of parturition and milk ejection and a major modulator of various social behaviors, including social recognition, aggression and parenting. In the past decade, there has been significant excitement around the possible use of oxytocin to treat behavioral deficits in neurodevelopmental disorders, including autism spectrum disorder (ASD). Yet, despite the fast move to clinical trials with oxytocin, little attention has been paid to the possibility that the oxytocin system in the brain is perturbed in these disorders and to what extent such perturbations may contribute to social behavior deficits. Large-scale whole-exome sequencing studies in subjects with ASD, along with biochemical and electrophysiological studies in animal models of the disorder, indicate several risk genes that play an essential role in brain synapses, suggesting that deficits in synaptic activity and plasticity underlie the pathophysiology in a considerable portion of these cases. Oxytocin has been repeatedly shown, both in vitro and in vivo, to modify synaptic properties and plasticity and to modulate neural activity in circuits that regulate social behavior. Together, these findings led us to hypothesize that failure of the oxytocin system during early development, as a direct or indirect consequence of genetic mutations, may impact social behavior by altering synaptic activity and plasticity. In this paper, we review the evidence that support our hypothesis.